2022
DOI: 10.1055/s-0041-1741456
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Premenstrual Syndrome and Associated Factors Among Academics of a University in Midwest Brazil

Abstract: Objective To investigate the prevalence of premenstrual syndrome (PMS) and premenstrual dysphoric disorder (PMDD) in university students, the factors associated with PMS, the most prevalent symptoms, and the interference of symptoms in academic, family, social, and work activities. Methods This cross-sectional study included 1,115 university students aged ≥ 18 years from the University of Rio Verde, Goiás. Premenstrual syndrome and PMDD were identified using the Premenstrual Symptoms Screening Tool. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 32 publications
0
7
0
2
Order By: Relevance
“…The incidence rate of this disorder was remarkably higher compared to other studies, where the incidence rate ranged between 35.6% and 80.5% in studies conducted on university students. [41][42][43][44] The most prevalent symptoms of PMS vary in frequency between populations. For example, in this study, the most common PMS symptom was backache (69%), followed by mood swings (68%) and tiredness (62%), while the most common symptom in the previously mentioned Rafique and Al-Sheikh study was mood swings (46%), followed by tiredness (43.5%) and generalized pains (37.4%).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of this disorder was remarkably higher compared to other studies, where the incidence rate ranged between 35.6% and 80.5% in studies conducted on university students. [41][42][43][44] The most prevalent symptoms of PMS vary in frequency between populations. For example, in this study, the most common PMS symptom was backache (69%), followed by mood swings (68%) and tiredness (62%), while the most common symptom in the previously mentioned Rafique and Al-Sheikh study was mood swings (46%), followed by tiredness (43.5%) and generalized pains (37.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these articles provide reliable data sources to better our understanding of PMS/PMDD, including incidence rate. In recent years, numerous studies have evaluated childhood body size and premenstrual disorders in young adulthood ( 36 ), comorbid bipolar disorder ( 37 ), prevalence, and associated factors among different groups ( 38 ). For instance, studies showed that the prevalence of PMS among Academics at a University in Midwest Brazil was 46.9% ( 38 ), and 21.1% for university students ( 39 ), which are higher than ever before.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, numerous studies have evaluated childhood body size and premenstrual disorders in young adulthood ( 36 ), comorbid bipolar disorder ( 37 ), prevalence, and associated factors among different groups ( 38 ). For instance, studies showed that the prevalence of PMS among Academics at a University in Midwest Brazil was 46.9% ( 38 ), and 21.1% for university students ( 39 ), which are higher than ever before. Moreover, risk factors for PMS/PMDD include childhood abuse and neglect ( 40 ), childhood maltreatment ( 41 ), and perinatal depression ( 42 ), among others.…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle modification and regular exercise may have a more pronounced positive effect in milder cases of PMS (16). At the same time, it is recommended to minimize the intake of salt, caffeine, and tobacco (15,(67)(68)(69). A study of students in the United Arab Emirates reported that fruit consumption was associated with a reduced risk of behavioral symptoms, and smoking and consumption of caloric foods (high in fat, sugar, and salt) were identified as risk factors vital for PMS (25).…”
Section: Impact Of Micronutrients and Herbal Supplementsmentioning
confidence: 99%